High proportion of tuberculosis recent transmission in rural areas of Northeastern China: a 3-year prospective population-based genotypic and spatial analysis in Hinggan League, China - Xichao Ou; Xiangchen Li; Shaojun Pei; Bing Zhao; Liping Feng; Chong Teng; Yewei Lu; Hanfang Zhu; Yang Zhou; Hui Xia; Zhengwei Liu; Xiaomeng Wang; et al. (Microbiology Spectrum)
ABSTRACT Tuberculosis (TB) remains a significant public health challenge in China, particularly in rural areas like Hinggan League (HL), Inner Mongolia. Understanding the genetic diversity and transmission dynamics of Mycobacterium tuberculosis (MTB) strains is crucial for effective TB control. We conducted a prospective study from 2021 to 2023, sequencing 221 MTB isolates from HL. After quality control, 210 cases were analyzed. The genomic clustering rate was calculated to evaluate the level of recent transmission. Risk factors were identified by logistic regression analysis. Geospatial analysis was conducted with kernel density estimation. The majority of strains belonged to sub-lineage 2.2.1 in lineage 2 (L2), also known as the Beijing family (89.0%, 187/210), while the remainder belonged to lineage 4 (L4). L2 strains showed greater genetic similarity and shorter branch lengths compared with L4 strains. The overall drug resistance rate was 21.9%, with six multidrug-resistant TB (MDR-TB) and five pre-extensively drug resistant TB (pre-XDR-TB) cases identified. Almost half of the strains belonged to putative transmission clusters within 10 SNPs. Logistic regression analysis identified living in Jalaid Banner and being infected by L2 strains as significant risk factors for recent transmission. Spatial analysis identified spatial aggregation of TB cases in the eastern region of HL, with a hotspot for recent transmission in Jalaid Banner. The temporal distribution of TB cases in HL exhibited seasonal fluctuations, with diagnosis rates peaking in the first half of each year, and a notable increase in clustered cases in 2022. This study provides insights into the molecular epidemiology and transmission dynamics of TB in HL. Our results underscore the ongoing problem of TB transmission in rural settings, indicating the need for targeted interventions. These findings are vital for informing TB control strategies in HL and similar settings.IMPORTANCETuberculosis (TB) remains a major public health problem in China. This study provides insights into the molecular epidemiology and transmission dynamics of TB in rural areas (Hinggan League [HL], Inner Mongolia) in China. Nearly half of the enrolled TB cases were attributed to recent transmission, a proportion higher than that observed in other rural areas in China (31.4%), highlighting the significance of recent transmission in driving the TB epidemic in this region. Only 19.6% of all drug-resistant TB (DR-TB) cases were found within putative transmission clusters, indicating a lower proportion compared with the previous studies, which indicated that DR-TB is more associated with the de novo evolution of resistance within patients. Spatial analysis showed that the TB epidemic was concentrated in densely populated areas in eastern HL. The findings identified epidemiological differences within HL, highlighting the importance of targeted interventions and surveillance to control the spread of TB in HL.